MENGUKUR FINANCIAL DISTRESS DENGAN METODE GROVER, ALTMAN Z-SCORE, SPRINGATE DAN ZMIJEWSKI PADA PT SOLUSI BANGUN INDONESIA TBK - Nur Kholifah; Djumali Djumali; Sri Hartono (JURNAL ILMIAH EDUNOMIKA, 2020)
The domestic cemenet industry was having income fluctuation since several years ago. Even in 2018 domestic cement’s sales had decreased if we compared it to the previous year. It caused by the decline of domestic cement demand, while the supply of domestic cement was very abundant. Each company certainly did some various strategies so that the company would not get any finance difficulty to keep survive in business competition and the company product could be consuments’s top choice. The same case happened to PT Solusi Bangun Indonesia Tbk which had comprehensive loss since 2016. The aim of this study is to examine the company’s health status or bankruptcy potential and see the difference of the prediction results of PT Solusi Bangun Indonesia Tbk in 2016-2018. There are 4 methods that applied in this research, they are Grover, Altman Z-Score, Springate and Zmijewski. The results indicate there is a difference betweet each prediction method. Grover, Altman Z-Score and Springate reveal that the company was in bankrupt condition. Meanwhile Zmijewski method shows that the company was in health condition. Keywords : Bankruptcy, Grover, Altman Z-Score, Springate, Zmijewski